Selective trapping of oligos to triangular gold nanoparticles utilizing dielectrophoresis - Andrejeff, Tanja (2014)
Triangular shaped particles are an interesting research topic since there are three plasmonically active tips, which can be utilized in new molecular sensing application systems. In this research we used dielectrophoretic force to trap thiol-modified (5’- end) and Cy3-dye-labeled (3’-end) single-stranded DNA (ssDNA) oligonucleotides, size 40 nt (about 22 nm long), to the corners of the gold triangles. These gold triangles were 20 nm thick and side length was 1 μm. The trapping experiment was done under AC-circuit and the gathering of the oligos to the triangles was studied in situ under confocal microscope. The theoretical values for dielectrophoretic force with different voltages were simulated with finite element method. Experimentally the required DEP-force was achieved by using about 40 Vpp voltage and in the simulation system with 34 Vpp. Most of the oligos formed “cloud” around the triangle and few of them trapped also on the corners. This “cloud” can be seen also in simulations, where the gathering of the oligos was modeled. At least, our research prove that gold triangles can be used for trapping biomolecules and hence also to sensing and detecting them.